A Real Options Model with Games Applied to the Rio de Janeiro Residential Real Estate Market - de Almeida, Glaudiane Lilian (2018)
Purpose – To determine the optimal investment strategy in Nash equilibrium for the residential real estate market of Rio de Janeiro, considering the uncertainty in the demand for real estate and the number of active competitors in the market. Design/methodology/approach – A Real Options Game model was developed. The parameters of the model were estimated with econometric tools using data from the Rio de Janeiro real estate market. Findings – The quantitative results obtained are intuitive in the sense that the larger the number of competitors, the lower the level of demand required for investment in new units, whereas the greater the volatility of demand, the greater the demand threshold for the investment to be optimal. Originality/value – This study modified the methodology of Grenadier (2002), providing a more adequate and robust specification of the uncertainty for the demand function, thus allowing more intuitive economic interpretations.